(Re)pensando el vínculo entre migración y crisis : perspectivas desde América Latina y Europa - Nejamkis, Lucila S.; Conti, Luisa, 1981-; Aksakal, Mustafa (CALAS, Maria Sibylla Merian Center ; CLACSO, 2021)
Over the years it has been shown that migrations are structural phenomena of our societies and not sporadic. However, in recent decades, both from governments, international organizations and academia, migrations have been associated with the concept of crisis. Why is human mobility still linked to the idea of an extraordinary event of modernity? Is migration a consequence of the crisis or a cause? How do different governments and international organizations construct the concept of migration crisis? Seeking to answer these and other questions, the chapters in this volume offer a critical look at the link between migration and crisis from different theoretical and geographical angles and invite us to rethink the limits of the very concept of migration crisis through twelve organized case studies. around the political analytical categories, environment and identity.